Transcriptional Immunoprofiling at the Tick-Virus-Host Interface during Early Stages of Tick-Borne Encephalitis Virus Transmission - Thangamani, Saravanan; Hermance, Meghan E.; Santos, Rodrigo I.; Slovak, Mirko; Heinze, Dar; Widen, Steven G.; Kazimirova, Maria (Frontiers in Cellular and Infection Microbiology, 2017)
Emerging and re-emerging diseases transmitted by blood feeding arthropods are significant global public health problems. Ticks transmit the greatest variety of pathogenic microorganisms of any blood feeding arthropod. Infectious agents transmitted by ticks are delivered to the vertebrate host together with saliva at the bite site. Tick salivary glands produce complex cocktails of bioactive molecules that facilitate blood feeding and pathogen transmission by modulating host hemostasis, pain/itch responses, wound healing, and both innate and adaptive immunity. In this study, we utilized Illumina Next Generation Sequencing to characterize cutaneous immune responses to Ixodes ricinus tick transmitted tick-borne encephalitis virus (TBEV). A comparative immune gene expression analysis of TBEV-infected and uninfected tick feeding sites was performed. Our analysis reveals that ticks create an inflammatory environment at the bite site during the first 3 hours of feeding, and significant differences in host responses were observed between TBEV-infected and uninfected tick feeding. Gene-expression analysis reveals modulation of inflammatory genes after 1 and 3 hours of TBEV-infected tick feeding. Chemokines and cytokines consistent with a neutrophil-dominated immune response are prominent. Immunohistochemistry of the tick feeding site revealed that mononuclear phagocytes and fibroblasts are the primary target cells for TBEV infection and did not detect TBEV antigens in neutrophils. Together, the genomic and immunohistochemistry results suggest early cutaneous host responses to TBEV-infected tick feeding are more inflammatory than expected and highlight the importance of inflammatory chemokine and cytokine pathways in tick-borne flavivirus transmission.